G248(P) Introducing live waiting times online as a service improvement for the paediatric emergency department (PED). (25th October 2020) - Menon, V; Wong, C
Abstract : Aims: Waiting times in Emergency Departments (ED) is a national problem. Using advancements in technology current live ED waiting times can be made available to the public, so that patients can decide whether to attend an ED or are better off seen in the community. Currently the hospital website displays live wait times for the adult ED but not for paediatric ED (PED). Seeing as the PED works as a separate entity to adult ED, it beckons the question, 'Is there a need for live PED wait times to be displayed to the public?' with the aim to introduce a service improvement to provide the information if required. Methods: This audit comprised of a mixed methods analysis. The audit recruited accompanying adults of child attendees at the hospital's PED. A questionnaire discussed the use of any other healthcare services and any existing knowledge of current wait times. Analysis included descriptive statistics and cross tabulation with χ2 test of independence. Results: Sixty participants completed the questionnaire. 53.2% had not used any other healthcare service before arrival. 93.5% did not know the wait time before attending and 77.4% answered it would be useful to know. More than 60% said that had they known that the website was providing information on wait times they would have checked it before coming to the ED. The association between displaying wait times online and checking the hospital website before attending was significant, χ2 (1, N = 61) = 6.18, P = 0.01. Conclusion: This audit recognised the need to add PED live waiting times onto the hospital website as a service improvement. The advantages to knowing about current PED waiting times include: Choosing to attend ED if the problem was urgent, or seek help from other services Reduced attendance reduces the number of breeches and pressure on the department Happier patients who at least know what to expect before attending Incorporation of live wait times on the hospital website for the PED is currently being designed.